2015
DOI: 10.1586/14760584.2015.1037743
|View full text |Cite
|
Sign up to set email alerts
|

PCVs in individuals at increased risk of pneumococcal disease: a literature review

Abstract: The use of pneumococcal conjugate vaccine (PCV) in childhood pneumococcal immunization programs successfully reduced the incidence of pneumococcal disease in children. Nonetheless, there remains a high burden of pneumococcal disease in adults, especially the elderly, and children/adults with chronic medical conditions. Two pneumococcal vaccines are currently available for adults at risk of pneumococcal disease: the 23-valent pneumococcal polysaccharide vaccine (PPV23) and the more recently licensed PCV13. As i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…These studies evaluated different regimens of either polysaccharide or conjugate and polysaccharide vaccines, and antibody titers were measured. These studies demonstrated that the administration of pneumococcal immunization prompted antibody responses in children with SCA, similar to responses seen among healthy children, and that there were no unexpected adverse events [12]. PCV13 substituted PCV7.…”
Section: Comments and Conclusionsupporting
confidence: 52%
“…These studies evaluated different regimens of either polysaccharide or conjugate and polysaccharide vaccines, and antibody titers were measured. These studies demonstrated that the administration of pneumococcal immunization prompted antibody responses in children with SCA, similar to responses seen among healthy children, and that there were no unexpected adverse events [12]. PCV13 substituted PCV7.…”
Section: Comments and Conclusionsupporting
confidence: 52%
“…Children 2 y of age and young adults with sickle cell anemia, Hodgkin disease, congenital or acquired immunodeficiency including Human Immunodeficiency Virus (HIV) infection, diabetes mellitus, nephrotic syndrome, as well as those with functional or anatomic asplenia, are at increased risk of developing invasive pneumococcal disease (IPD) in comparison to healthy individuals without these conditions. [5][6][7][8][9][10] The most common PD syndromes include pneumonia (approximately 75%), bacteremia without focus (approximately 20%), and meningitis (approximately 5%). Generally, these syndromes are classified as IPD and pneumococcal pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody-mediated immune responses are important in protection against bacterial respiratory pathogens that cause OM and exacerbations of COPD, namely, nontypeable Haemophilus influenzae (NTHi) and Streptococcus pneumoniae, both of which occupy the same ecological niche as M. catarrhalis (23)(24)(25)(26)(27). Therefore, although the correlate(s) of protection against M. catarrhalis has not been identified, given the parallels with NTHi and S. pneumoniae infection, antibody-mediated immune responses have been implicated as an important mediator of protection for M. catarrhalis, as well.…”
Section: Discussionmentioning
confidence: 99%